(untitled) (Jurnal Ilmu-ilmu Perikanan dan Budidaya Perairan)
The epidemic of Koi Herves Virus (KHV) infected most of carps culture in Musi Rawas Regency of South Sumatra, in February 2003. The disease was supposedly came from West Java, the earlier KHV infected area: by the cross-province fish trader. The disease caused approximately 7,5 billion rupiah loss derving from 813,726 kg of fish and 1,3 million seeds. Eventhough a seminar on all aspects to overcome the disease was held on site in February 25th 2003, it was inadequate. A synergized work among the stakeholders (government, fishfarmers, public) on increasing seed and feed controlling quality should be strengthened. The objective of this article is to contribute technical advise on prevention KHV disease in the future. Keywords : epidemic, Koi Herves Virus, problem solutions